BACTERIAL PROFILE AND ANTIBIOTIC SUSCEPTIBILITY PATTERNS IN HOSPITALIZED PATIENTS WITH INFECTED DIABETIC FOOT - Hammad, Aseel (An-Najah National University, 2025)
Background: Diabetes mellitus (DM) represents a major public health concern and has been increasingly associated with serious complications. One of the most complex and costly complications of diabetes is diabetic foot infection (DFI). Early diagnosis, promote an appropriate treatment based on pathogen identification and antibiotic susceptibility testing, is essential for achieving favorable clinical outcomes. The aim of this study is to assess the bacterial profile and antibiotic susceptibility patterns in patients with infected diabetic foot. Methodology: A retrospective design to evaluate bacterial profile and antibiotic susceptibility patterns in patients with infected diabetic foot ulcers (DFUs) was used. The study was conducted at Salfeet Governmental Hospital. The files of all type 2 diabetes mellitus patients who meet the inclusion criteria during the previous three years were included. Statistical Package for Social Sciences (SPSS) was used for data analysis. Results The study included 211 participants, in which the majority (45.0%) aged between 50-59 years, & males comprised 66.8% of the sample. Regarding diabetes mellitus (DM) duration, most participants (87.2%) had been diagnosed for > 10 years. Neuropathy was present in 34.6%, nephropathy in 24.6%, and angiopathy in 8.5% of the study population. Among the study participants, the most common ulcer site was the forefoot (33.1%). Ulcers penetrating to the bone (Grade D) were present in 20.4% of cases, and 7.1% had ulcers with osteomyelitis or abscess (Grade E). A statistically significant association was found between nephropathy and severity of ulcer grade (p = 0.007). The most commonly isolated microorganism was Escherichia coli, detected in 26.5% of cases, followed by Staphylococcus aureus (20.9%) and Pseudomonas aeruginosa (10.9%). Among the antibiotics tested for sensitivity, Meropenem/Ertapenem showed the highest sensitivity, with 63.03%, followed by Amikacin at 47.39%, Gentamycin (40.28%), and Piperacillin+Tazobactam (39.81%). Amoxicillin + Clavulanic acid showed the lowest sensitivity, at only 3.79%, Conclusion: The microbiological profiles revealed a high prevalence of Gram-negative bacteria, notably Escherichia coli, and Pseudomonas aeruginosa, accompanied by considerable treatment resistance. Meropenem, was the most often prescribed and effective antibiotic. The results affirm the necessity for multidisciplinary management strategies that encompass early detection, prompt surgical and antimicrobial interventions to enhance clinical outcomes and reduce amputations.
الملف البكتيري وأنماط حساسية المضادات الحيوية لدى المرضى المقيمين في المستشفى المصابين بالتهاب القدم السكري